Science of fat - Ronald M. Evans, lecturer; Jeffrey M. Friedman, lecturer (Howard Hughes Medical Institute, 2005)
In four thought-provoking presentations, Dr. Ronald M. Evans and Dr. Jeffrey Friedman discuss the complex biological systems that control body weight and energy metabolism--and how a better genetic understanding of these processes could lead researchers to treatments that curb obesity and improve public health.